Taxonomy and nomenclature of seven names in Bacidia (Ramalinaceae, Lecanorales) described from Russia - Gerasimova, Julia V.; Ekman, Stefan (Phytotaxa, 2017)
We aim to increase understanding and improve taxonomy of seven names currently treated in Bacidia that were described from Russian territory based on material collected during 19th-century expeditions: Bacidia alborussula, B. freshfieldii, B. graminum, B. indigens, B. primigenia, B. subabbrevians, and B. xylophila. B. alborussula, B. graminum, and B. indigens are transferred here to Haematomma, Lecania, and Bacidina, respectively. Bacidia freshfieldii and B. subabbrevians belong in the Ramalinaceae and are provisionally kept in Bacidia even though none of them is congeneric with the type of that genus. B. primigenia belongs in Arthrorhaphis, but we refrain from making any new combination owing to its questionable status as a species distinct from A. grisea. B. xylophila is a younger synonym of Lecania subfuscula. We designate lectotypes for names previously not typified and for which syntypes exist: Lecidea alborussula, L. graminum, L. indigens, and L. subabbrevians.